CEO’s Technology Knowledge Towards E-Commerce Adoption: Perspective of Small and Medium Enterprises (SMEs) - Sin, Kit Yeng; Azuddin, Bahari; Abdullah, Osman; Hanum, Hassan; Ling, Sim Choon; Jin, Lim Yi; Safizal, Abdullah (American Scientific Publishers, 2016)
Electronic commerce (E-commerce) is gaining attention among practitioners and researchers in last two decades particularly among small and medium enterprises (SMEs). Seeing that E-commerce adoption among Malaysian SMEs is still in infant stage and the participation of enterprises in implementation of E-commerce is insignificant, this study aims to analyze the prime key factor of E-commerce adoption among SMEs in Northern state of Malaysia. CEO’s technology knowledge is specifically conducted in this research. Above and beyond, this study is conducted based on survey design and descriptive research investigation. Approximately 400 questionnaires are distributed to CEOs or managers diversified from different sectors but only 291 questionnaires were obtained. The research data is analyzed using frequency analysis, reliability analysis, descriptive analysis, as well as correlation analysis.